ISLAM AND LOCAL CULTURE (Living Qur'anic Studies In The Ngeruwat Bumi Culture In Balung Village) - Sa’diyah, Miftahus (STAIN PAMEKASAN, 2018)
This paper tries to explain the phenomenon that has become a tradition of Muslim society. A tradition that presents the Qur'an in the midst of people's life or it is referred to as